Initial design and validation of Google Sites-based physics learning media on thermodynamics - Hidayatul Aula; Suci Prihatiningtyas; Ino Angga Putra; Syamsudin Syamsudin; Ayu Sekar Pertiwi (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This research aims to develop Google Sites-based learning media on Thermodynamics material and test its feasibility through expert validation. The research method used is research and development (R&D) based on the Borg and Gall model, but it is limited to the fifth stage. The development process includes identifying potential and problems, data collection, product design, validation by experts, and revision. The media was developed in the form of an interactive learning site that contains Thermodynamics material, learning videos, practice questions, AR, e-LKPD, and Augmented Reality (AR) content. Validation was carried out by a material expert and a media expert using a questionnaire in the form of a rating scale. The results of the data analysis show that the Google Sites-based learning media obtained a